1996
DOI: 10.1111/j.1752-0606.1996.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Lenses: Variations in Clients’ Perception of Family Therapy by Race and Gender

Abstract: Race and gender have been given extensive theoretical and clinical attention in family therapy in the last decade. However, little empirical work has focused on their effect on therapy. The present study examines the effect of clients’ race and therapists’ race and gender on male and female partners’ assessments of an initial and subsequent family/marital therapy session. One hundred twenty‐six individuals, comprising 63 heterosexual adult couples, evaluated both the first and the fourth therapy session using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…(2004) report that in research since 1990 there are small effect size enhancements when Mexican American and Asian American therapists and clients are matched. While not a true outcome study, Gregory and Leslie (1996) found Black females (but not males) rated initial MFT sessions with White therapists more negatively than with Black therapists, but these differences vanished by the fourth session. An old but very large sample ( N = 3,956) MFT study (Beck & Jones, 1973) found that Black clients were significantly more likely to drop out if assigned to White counselors, whereas there was no impact when White clients were assigned to Black counselors.…”
mentioning
confidence: 73%
“…(2004) report that in research since 1990 there are small effect size enhancements when Mexican American and Asian American therapists and clients are matched. While not a true outcome study, Gregory and Leslie (1996) found Black females (but not males) rated initial MFT sessions with White therapists more negatively than with Black therapists, but these differences vanished by the fourth session. An old but very large sample ( N = 3,956) MFT study (Beck & Jones, 1973) found that Black clients were significantly more likely to drop out if assigned to White counselors, whereas there was no impact when White clients were assigned to Black counselors.…”
mentioning
confidence: 73%
“…Gregory and Leslie (1996) however found a gender and ethnicity interaction when evaluating premature termination rates, with AA females treated by EA therapists exhibiting more negative impressions of initial therapy sessions than did EA females who were treated by an AA therapist. However, when analyzing males, it was discovered that when compared to their EA counterparts, AA males were found to report more positive ratings of initial therapy sessions.…”
mentioning
confidence: 78%
“…As well, the significance of the engagement process in cross-cultural psychotherapy has been repeatedly emphasized (Cardemil and Battle 2003;Coleman 2002;Constantine 2002;Dyche and Zayas 1995;Erdur et al 2003;Keenan 2001;Keenan et al 2005;Horvath 2006;La Roche and Maxie 2003;Lee 2008;Mishne 2002;Seeley 2000;Shonfeld-Ringel 2000;Stuart 2004;Sue 2006). Engagement is seen as critical to a client's decision to continue with or drop out of treatment (Gregory and Leslie 1996;Frank et al 1987). Although it can be considered part and parcel of the developing therapeutic relationship, a successful engagement process is not equivalent to a good relationship.…”
Section: Therapeutic Alliance and The Engagement Processmentioning
confidence: 99%